Under Influence Policies of local division under influence in Senegal: incompleteness, hybridization, fragmentation - (:unkn) unknown (My University, 2020)
Gridding, separating, dividing the continuous space of societies: according to which dotted lines, which contours, which thresholds? The questioning is open and geography has not finished questioning the divisions. In contexts where the material delimitation and cartography of local territories are as yet unfinished, or even impracticable, for various reasons, the operations of division remain part of the discourse, but not without effects in local spaces. In West Africa, the immateriality of territorial delimitations was revealed in the light of the decentralization reforms undertaken by several countries at the turn of the 1990s. This discrepancy, between the effectiveness of the division on paper and the absence of delimitation, raises the question of the nature of the West African social space, particularly in the Sahel. Consequently, the analysis of the political division of local space draws on the analyses of Achille Mbembé on "itinerant territoriality" and those of Denis Retaillé on "mobile space" in the Sahel. The territory of Senegal, which is a product of "colonial manufacture" is struggling to free itself from the weight of this heritage. The most recent reshuffles of the local division since 2014 within the framework of Act 3 of Decentralization provide an opportunity to reconsider the interference of these reticular configurations in the territorialization of local authorities, while the Senegalese state is attempting, in a final episode, to build a coherent map of the national territory, which is still in touch with centrifugal dynamics. This article therefore sets out to explore the hypothesis that the local division of power in this country, particularly through the promotion of full communalization since 2014, reflects a territorialization of power in which the role of social networks, from village territories to the multisituated territories of migrants, proves to be decisive. This permanent tension between the division of local sp
Keywords: African Research